FaktorâFaktor Yang Dapat Mempengaruhi Pemahaman Atas Informasi Akuntansi Terhadap Persepsi Para Pelaku Pengrajin Tahu Didaerah Kecamatan Kartasura - Darnawan, Nanang; Ismunawan, Ismunawan (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
Understanding of accounting information is one of the companys activities to determine the extent of its business development and as a decision making for businesses to determine the policy to be taken, accounting is an indicator of operating performance in declsion-niakirq2 so as to Improve the management of the business of the small and medium businesses can identify and predict problems that arise in order to quickly take timely policy. Â Issues in this study include whether the knowledge, the attitude of the offender, and motivation affect the perception of the industry players in the area ofsmall artisans knows Kartasura district. The purpose of this study was to determine the effect of accounting knowledge, attitudes and motivations of the perpetrators of the perceptions of business people on understanding the accounting information partially or simultaneously. Analysis and research methods in research on industrial business craftsmen know who was in the area Kartasura districts with a sample of 60 artisans out using quota sampling method. The data collection method using questionnaires with multiple linear regression analysis, t test, F test, and coefficient determination (R2) which is accompanied with the analysis of the classical assumptions. Partial results analysis, accounting knowledge, attitudes, motivation arid long efforts positively influence the perception of UKM over accounting, information this is evident from the value of each variable of t count > t table (2.005) with the significance of each variable < 0,05. Both variables simultaneously also a positive effect on the perception of SMEâs over accounting information. This is evident from the value of F count (75.903) > F table ( 2.78 ) with significance 0.000 < 0,05. The accounting knowledge, attitudes, motivation and long effort by 83.5% influences on the perception of UKM on understanding the accounting information. Based on the analysis it can be concluded among other things that buiness people have an understanding of the craftsmen know that positive accounting information to the perception of the perpetrator knows, and the attitude and motivation of actors in the decision making attempt to determine the progress and development of their business.As for the suggestion that the author can give the actors are expected to include craftsmen know more detail in understanding the accounting information in decision making.